Effects of Valence and Extremity of eWOM on Attitude toward the Brand and Website - Lee, Mira; Rodgers, Shelly; Kim, Mikyoung (Journal of current issues and research in advertising, 2009)
Two studies were conducted to examine the influence of valence and extremity of consumer product reviews on attitude toward the brand and attitude toward the website. Each experiment was a one factor (valence/extremity: extremely negative, moderately negative, extremely positive) between-subjects design with a control group. Results in both studies showed that although extremely positive reviews increased attitude toward the brand, even a moderate amount of negativity negated this effect. Moreover, extremely negative reviews had a stronger influence on attitude toward the brand than either moderately negative reviews or extremely positive product reviews, thus supporting both negativity and extremity effect. Findings also show that varying degrees of brand review valence and extremity influenced attitude toward the website depending on website type (i.e., retailer vs. brand).